2020
DOI: 10.3390/microorganisms8071055
|View full text |Cite|
|
Sign up to set email alerts
|

Multidrug-Resistant Streptococcus agalactiae Strains Found in Human and Fish with High Penicillin and Cefotaxime Non-Susceptibilities

Abstract: Penicillin non-susceptible Streptococcus agalactiae (PEN-NS GBS) has been increasingly reported, with multidrug-resistant (MDR) GBS documented in Japan. Here we identified two PEN-NS GBS strains during our surveillance studies: one from a patient’s wound and the other from a tilapia. The patient’s GBS (H21) and fish GBS (F49) were serotyped and tested for antibiotic susceptibility. Whole-genome sequencing was performed to find the sequence type, antimicrobial resistance genes, and mutations in penicillin-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
1
18
0
2
Order By: Relevance
“…Increased use of antimicrobials for prophylaxis without proper bacteriological screening is one factor that raises this concern [ 21 ]. GBS is becoming resistant to different antibiotics, including macrolides and lincosamides, and recently resistance to penicillin and fluoroquinolone was also reported [ 22 ]. A systematic review and meta-analysis conducted in China showed that significant rates of resistance to erythromycin, clindamycin, and tetracycline were observed; 0–86%, 4–84%, and 23–96%, respectively [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased use of antimicrobials for prophylaxis without proper bacteriological screening is one factor that raises this concern [ 21 ]. GBS is becoming resistant to different antibiotics, including macrolides and lincosamides, and recently resistance to penicillin and fluoroquinolone was also reported [ 22 ]. A systematic review and meta-analysis conducted in China showed that significant rates of resistance to erythromycin, clindamycin, and tetracycline were observed; 0–86%, 4–84%, and 23–96%, respectively [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of resistance against erythromycin in the bacteria includes changes of the ribosomal target by a methylase [ 49 , 59 ]. It is important to search for other options for infection control [ 50 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second is that 23rRNA methylase can catalyze 50s ribosome and change the target position [13,23]. Methylase is coded by erm gene, which can lead to structural change of ribosome and make the Streptococcus agalactiae resistant to erythromycin [26,27].…”
Section: Discussionmentioning
confidence: 99%